2014
DOI: 10.5152/tjg.2014.7083
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus genotype distribution in Turkey remains unchanged after a decade: Performance of phylogenetic analysis of the NS5B, E1, and 5’UTR regions in genotyping efficiency

Abstract: Background/Aims: Hepatitis C virus (HCV) genotyping has a considerable effect on therapy. The aim was to determine the change in prevalence of HCV genotypes in Turkey during the last decade and to compare the performance of DNA sequencing of different targets in the HCV genome (NS5B, E1, and 5'UTR). Materials and Methods: Five hundred HCV RNA-positive patients (226 males, 274 females) were included in the study. The NS5B, E1, and 5'UTR regions of the HCV genome were amplified by polymerase chain reaction (PCR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 28 publications
0
7
0
1
Order By: Relevance
“…The most common genotype in Southern Israel was genotype 1b (62%) while genotype 4 (78%) was predominant in the Gaza Strip [61] . Turkey serves as a bridge between Europe and Asia, and HCV genotype pattern is similar to Eastern and Southern European countries, having genotype 1b as the most frequent genotype (> 70%) followed by genotype 1a [62] . HCV genotype 3a is the most common subtype in Iran followed by genotype 1a, 1b and 4 [63] .…”
Section: Chronic Hepatitis Cmentioning
confidence: 99%
“…The most common genotype in Southern Israel was genotype 1b (62%) while genotype 4 (78%) was predominant in the Gaza Strip [61] . Turkey serves as a bridge between Europe and Asia, and HCV genotype pattern is similar to Eastern and Southern European countries, having genotype 1b as the most frequent genotype (> 70%) followed by genotype 1a [62] . HCV genotype 3a is the most common subtype in Iran followed by genotype 1a, 1b and 4 [63] .…”
Section: Chronic Hepatitis Cmentioning
confidence: 99%
“…HCV genotype 1b was the most prevalent subtype in Turkey. A study comprising 500 patients that investigated the phylogenetic analysis of HCV-infected patients showed that HCV genotype 1b remained the most prevalent type throughout the previous decade (13). In Turkey, there is no national screening program for HCV.…”
mentioning
confidence: 99%
“…In Iran, located in the Middle East, there has been regional reports on hepatitis genotyping among infected patients. Compared to the studies of Iran's neighboring countries, it can be understood that the most common genotype is G1, found in approximately 50% to 75% of samples from Turkey and Bahrain (26)(27)(28). No study is available on HCV genotypic variation from Iran, Bahrain, and Pakistan, which could give cohesive circulation of HCV genotypes.…”
Section: Ast (Iu/l)mentioning
confidence: 93%